Success Factors of PMO Implementation for UAE Project-Based Organizations - Ghani Al Khoori, Abdulla Ali Abdul; Abdul Hamid, Mohd Syaiful Rizal (International Journal of Sustainable Construction Engineering and Technology, 2022)
In current competitive market, organisations strive not only to complete projects on time, but also to ensure stakeholder satisfaction. Creating a separate body or department for project management within an organisation is frequently motivated by a desire to improve project management and reduce projects that fall short of customers’ and stakeholders’ expectations due to budget overruns or intolerable delays. Thus, Project management Office (PMO) practises are becoming more popular around the world to support project management activities. Hence, this paper presents a qualitative approach by interviewing twenty experienced personnel who had worked with PMO for several years. The experts were from four organisation namely Masdar Abu Dhabi Future Energy Company, Al Mansouri 3B Group, Abu Dhabi Securities Exchange (ADX), and Gulf Falcon Company (GFC). These open interview sessions were to discover the success factors in implementing PMO in UAE organisation. The results of the interview found that there are six key factors affecting the effective implementation of the PMO which are project flexibility; politics and change resistance in stakeholders; alignment and accountability; efficient resources; risk management; effective leadership and team management. Project flexibility, as well as effective leadership and team management, are cited as the most critical factors by all respondents. The paper also incorporates an effective PMO framework which suggests various strategic measures to implement in five phases of the project lifecycle: initiation, planning, execution, monitoring and controlling, closing, and post-implementation reviewing.